What color is your paratext? trust metrics - Bilder, Geoffrey W. (Henry Stewart Talks, 2012)
What's this got to do with us?, The internet trust problem, Internet vs. scholarly trust, The researcher problem, Successfully dealing with trust on the internet, Gaming the system, What can we learn from the past?, The rise of meta-brands, The early modern internet